Simplify cosθ1+sinθ+1+sinθcosθ.


Answer:

2sec θ

Step by Step Explanation:
  1. \begin{align} & \dfrac{\cos \theta } { 1 + \sin \theta } + \dfrac{ 1 + \sin \theta } { \cos \theta } \\ = & \dfrac{\cos \theta \cos \theta + (1 + \sin \theta) ( 1 + \sin \theta)} { (1 + \sin \theta) \cos \theta } \\ = & \dfrac{\cos^2 \theta + 1 + \sin^2 \theta + 2 \sin \theta}{ (1 + \sin \theta) \cos \theta } \\ = & \dfrac{2 + 2 \sin \theta} {(1 + \sin \theta) \cos \theta } \\ = & \dfrac{2 (1 + \sin \theta)} {(1 + \sin \theta) \cos \theta } \\ = & 2sec θ \end{align}

You can reuse this answer
Creative Commons License